2022
DOI: 10.5194/hess-26-3377-2022
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning rainfall–runoff predictions of extreme events

Abstract: Abstract. The most accurate rainfall–runoff predictions are currently based on deep learning. There is a concern among hydrologists that the predictive accuracy of data-driven models based on deep learning may not be reliable in extrapolation or for predicting extreme events. This study tests that hypothesis using long short-term memory (LSTM) networks and an LSTM variant that is architecturally constrained to conserve mass. The LSTM network (and the mass-conserving LSTM variant) remained relatively accurate i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(82 citation statements)
references
References 37 publications
4
78
0
Order By: Relevance
“…Machine learning methods provide great versatility (Shen, 2018;Shen et al, 2018;Reichstein et al, 2019) and have demonstrated unprecedented accuracy in various modelling tasks like predictions in ungauged basins (PUB; e.g. Kratzert et al, 2019b;Prieto et al, 2019), transfer learning to data-scarce regions (Ma et al, 2021) or flood forecasting (Frame et al, 2022;Nevo et al, 2022). Nonetheless, deep learning remains a field of progress with gaps to fill.…”
Section: Machine Learning In Hydrologymentioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning methods provide great versatility (Shen, 2018;Shen et al, 2018;Reichstein et al, 2019) and have demonstrated unprecedented accuracy in various modelling tasks like predictions in ungauged basins (PUB; e.g. Kratzert et al, 2019b;Prieto et al, 2019), transfer learning to data-scarce regions (Ma et al, 2021) or flood forecasting (Frame et al, 2022;Nevo et al, 2022). Nonetheless, deep learning remains a field of progress with gaps to fill.…”
Section: Machine Learning In Hydrologymentioning
confidence: 99%
“…Yet, internal investigation of machine-learning models relies on additional methods that come with their own assumptions and caveats, and the current straightforward interpretability of conceptual models serves as a benchmark in the hydrologic community. Much environmental research is dedicated toward extrapolation in space and in time and of boundary conditions, in order to investigate extreme events (Frame et al, 2022), climate change projections (Nearing et al, 2019) and so on. In all these fields, ease of interpretability is desirable.…”
Section: Machine Learning In Hydrologymentioning
confidence: 99%
“…ML methods are an integral and critical part of the river stage forecasting and flood inundation models. For stage forecasts, it has already been shown that LSTMs outperform standard hydrological models, not just for gauged basins but also for ungauged basins (Kratzert et al, 2019a, b) and even for extreme out-of-training events (Frame et al, 2022). For inundation modeling, a comparison of the two ML-based inundation models with the physics-based hydraulic model found the ML models exhibited higher accuracy (Table 1).…”
Section: Discussionmentioning
confidence: 92%
“…This has yet to be applied to a large-sample LSTMs in regionalization, but it is possible that some research will elucidate this in the near future. Furthermore, some studies have started investigating the possibility of adding physical constraints within the LSTM structure (such as ensuring mass-balance) (Frame et al, 2022;Hoedt et al, 2021), which might pave the way to a better understanding of the underlying relationships built within the LSTM structure. Another limitation is the need for long observation data time series to adequately train the LSTM models.…”
Section: Comparison Of Hydrological Model-based and Lstm Regionalizationmentioning
confidence: 99%
“…On half their test catchments, the RNNs performed better than GR4H after training on a 14-year window, and for the other catchments the RNNs still performed acceptably well. With respect to the extrapolation to extreme events problem, Frame et al (2022) showed that LSTM models are relatively accurate at producing high flows when compared to SAC-SMA and a process-based model (US National Water Model), even when extreme events were excluded from the training. This suggests that LSTM models are able to not only extract relevant hydrological information from the training dataset but actually learn from it.…”
mentioning
confidence: 99%